EFFICIENCY OF THE DEVELOPMENT AND ORGANIZATIONAL AND ECONOMIC STIMULATION OF BUSINESS ACTIVITIES IN AGRICULTURE (American Journal of Business Management, Economics and Banking, 2024)
Today, the author gives feedback on the effectiveness of the development of business activities in agriculture and the organizational and economic incentives in our country and has developed scientific proposals and recommendations.